Recent decline in cod stocks in the North Sea–Skagerrak–Kattegat shifts the sources of larval supply. (May 2016) - Jonsson, Per R.; Corell, Hanna; André, Carl; Svedäng, Henrik; Moksnes, Per‐Olav
Abstract: Cod stocks in the North Sea, including the Kattegat and the Skagerrak, have declined dramatically since the 1970s. Occasionally there is a high recruitment of juveniles in Kattegat/Skagerrak, without leading to the rebuilding of adult cod stocks despite reduced fishing mortality. In a biophysical model of egg and larval drift, we examined the potential importance of extant and historical spawning grounds for recruitment of cod in the Kattegat/Skagerrak seas using data of spawning stock biomass from the 1970s and from today's reduced stocks. The results suggest that Kattegat in the 1970s relied on largely locally retained (83%) larvae with little annual variation in recruitment. Kattegat also provided a substantial proportion of larvae recruiting in Swedish Skagerrak (72%). This is in contrast to present conditions where the Kattegat spawning stock has been reduced by 94%, and Kattegat only provides 34% of locally retained larvae and 30% to Swedish Skagerrak. Instead, the protected area in the Öresund and the Belt Sea are expected today to provide most larvae recruiting in Kattegat. Also, the inflow of larvae from the North Sea to Skagerrak and Kattegat can be significant although highly variable between years, with a positive correlation to the North‐Atlantic Oscillation index (NAO). The rebuilding of healthy spawning areas in the Kattegat may be key for restoring local cod stocks in both Kattegat and along the Skagerrak coast. This poses a management challenge if cod with local 'Kattegat' adaptations, e.g., in terms of egg density and migration patterns, are lost or reduced to non‐resilient densities.